جذور نظرية الحقول الدلالية في معجم فقه اللغة وسر العربية للثعالبي - دراسة تأصيلية تجديدية - زواوي, ليندة (University of Eloued جامعة الوادي, 2021)
إن اللغة العربية لها ثروة لفظية زاخرة لا تعد ولا تحصى، واهتمام اللغويين قديما بالبحث في دلالة كلماتها قادهم إلى أعمال مبكرة تعد من صميم البحث الدلالي الحديث، نجد منها معجم "فقه اللغة وسر العربية" للثعالبي، فرغم اختصاره فهو شامل محيط؛ وهذا راجع للهدف الذي أُلّف من أجله وهو تصحيح أساليب المتكلمين بسبب ما دب من شيوع اللحن في معاني الكلمات في عصره، فأتى بما يصحح ذلك متوخيا الدقة في المدلول والتخصيص في المعنى. إن هذا البحث يهدف إلى إبراز القيمة العلمية لهذا المعجم، وربطه بما توصل إليه الغربيون في هذا المجال لنصل إلى إعادة صياغة الجهود المؤسسة لنظرية الحقول الدلالية عند العرب. وإذا جئنا نؤرخ لهذه النظرية عند العرب لا نجد في التراث اللغوي العربي ما يشير لذلك لأنهم لم يطلقوا عليها المصطلح نفسه، إضافة إلى أنها بقيت حبيسة الرسائل اللغوية ومعاجم المعاني ولم تتطور عبر العصور حتى جاء الغربيون وأضافوا إبداعاتهم إلى هذا التراث الضخم لتحقيق عصرنة عمل القدماء العرب، وبناء على ما سبق ذكره البحث سيحاول الإجابة على السؤال التالي : ماهي جوانب نظرية الحقول الدلالية في معجم فقه اللغة وسر العربية للثعالبي؟. Arabic has countless verbal wealth. The interest of ancient linguists in researching the significance of its words led them to the early works which are at the core of the semantic research. From it, we find the Lexicon of Jurisprudence and the Secret of Arabic for Thaalibi. Despite its concision, it is a comprehensive perimeter. This is due to the goal to what he wrote it for, which is to correct the methods of the speakers because of the prevalence of the melody in the meanings of the words in his era. Hence, he came up with what is correct for the sake of precision and specialization in the meaning. This research aims at highlighting the scientific value of this dictionary and links it to what Westerners have reached in this field so that we can reformulate the founding efforts of semantic fields theory among Arabs. If we came to chronicle this theory with the Arabs, nothing is found in the Arab linguistic heritage to indicate this since they did not term it similarly. In addition, it remained locked in linguistic messages and semantic glossaries and did not develop throughout the ages until westerners added their creativity to this vast heritage to achieve modernization of the ancient Arab works. Based on the foregoing, this research attempts to answer the following question: what are the aspects of semantic field’s theory in the Lexicon Jurisprudence and the Secret of Arabic to Thaalibi.
مداخلة. الملتقى الدولي: النص التراثي العربي في منظورات الحداثة وما بعدها، الحدود، التصورات، الإشكالات. كلية الآداب واللغات. جامعة الشهيد حمه لخضر – الوادي
Keywords: علم الدلالة، المعنى، الحقل الدلالي، الحقول السنتجماتية، الحقول الصرفية; semantics, semantic field, meaning, syntagmatic fields, morpho semantic fields